Prospect studies and geological CO2 storage potential in Nigeria - Victor Omefe; Mahlon Kida Marvin; Zakiyyu Muhammad Sarkinbaka; Victor Inumidun Fagorite; Aliyu Buba Ngulde (Unconventional Resources)
Nigeria's dependence on fossil fuels has resulted in high CO2 emissions. However, while the country's Nationally Determined Contribution (NDC) outlines a 20–47 % reduction in greenhouse gas emissions, the lack of enabling investment mechanisms and limited technological innovation continue to hinder the deployment of Carbon Capture, Utilization, and Storage (CCUS) technologies. Successful implementation of CCUS in Nigeria will depend on a combination of critical factors. These include the suitability and efficiency of the carbon capture technologies deployed, the level of technical readiness and local capacity, the economic feasibility in terms of operating and capital costs, and the integration of comprehensive life cycle assessments to ensure environmental and economic sustainability.A recent study by the International Finance Corporation (IFC) estimated that Nigeria has a theoretical storage potential of about 10.7 gigatons. However, our review of basin-specific studies suggests that this estimate may be conservative while highlighting the Niger Delta as the most viable region for large-scale CO2 sequestration. Despite these indicators, the absence of commercial-scale CCUS deployment, along with weak regulatory support and a lack of fiscal incentives, remain significant obstacles. The findings argue for a focused policy shift that leverages Nigeria's existing oil and gas infrastructure, enabling the clustering of CO2 point sources to share transportation and injection facilities. Furthermore, expedited strategic partnerships with initiatives such as the Africa Carbon Markets Initiative (ACMI) could facilitate carbon credit development and improve economic viability. Pilot studies already demonstrate promising storage performance, supporting the argument for near-term demonstration projects. We highlight that with appropriate policy support, technology deployment, and international collaboration, geological CO2 storage could play a critical role in Nigeria's trajectory toward climate and sustainable energy development. We offer practical recommendations for aligning CCUS deployment with national climate goals and enhancing investment readiness in the sector.